Effective control of postoperative recurrence of pregnancy-related gastric cancer using anti-PD-1 as a monotherapy: a case report - Liu, Xu; Li, Xiaoqi; Zhu, Chunchao; Ji, Linhua (Frontiers in Oncology, 2024)
Pregnancy-related gastric cancer is characterized by a refractory nature and poor prognosis; few gastric cancer cases during pregnancy achieved acceptable outcomes by using anti-PD-1 as a monotherapy. A 32-year-old pregnant female patient was admitted to the emergency department of the obstetrics and gynecology department and eventually diagnosed with gastric cancer. Radical surgery for gastric cancer was conducted after the termination of pregnancy. At 1-year postoperative follow-up, tumor recurrence was revealed. This patient has achieved a decrease in tumor burden after receiving anti-PD-1 as a monotherapy. This case documents tumor response to PD-1 monotherapy in pregnancy-related gastric cancer and highlights the potential for future use in specific clinical scenarios.